2014
DOI: 10.1074/jbc.m114.588871
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Induced Neural Stem Cells for Spinal Cord Injury

Abstract: Background:The therapeutic potential of induced neural stem cells (iNSCs) that are directly converted from fibroblasts still remains elusive. Results: Engrafted iNSCs enhance functional recovery after spinal cord injury in the rat model. Conclusion:The directly converted iNSCs hold therapeutic potential. Significance: This is the first report describing the therapeutic potential of iNSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 29 publications
8
68
0
1
Order By: Relevance
“…6C). As in our previous transplantation studies (13,20), here we found no obvious evidence for tumor formation in any of the transplanted rats (data not shown). To further investigate the fate of the engrafted e-iNSCs, we checked for the presence of Nestin, a progenitor marker, but found no GFP-positive cells expressing Nestin, indicating that the engrafted e-iNSCs had lost their stem cell identity (Fig.…”
Section: Single Transfection Of Episomal Vectors Is Sufficient For Gesupporting
confidence: 89%
See 2 more Smart Citations
“…6C). As in our previous transplantation studies (13,20), here we found no obvious evidence for tumor formation in any of the transplanted rats (data not shown). To further investigate the fate of the engrafted e-iNSCs, we checked for the presence of Nestin, a progenitor marker, but found no GFP-positive cells expressing Nestin, indicating that the engrafted e-iNSCs had lost their stem cell identity (Fig.…”
Section: Single Transfection Of Episomal Vectors Is Sufficient For Gesupporting
confidence: 89%
“…Finally, to understand this gradual process on the epigenetic level, we next checked the DNA methylation status of both Nestin, a NSC marker (19), and Col1a1, a fibroblast marker (13). Notably, the promoter region of Col1a1 was dramatically de novo methylated even in the early passage e-iNSCs to the level similar to control NSCs (Fig.…”
Section: Single Transfection Of Episomal Vectors Is Sufficient For Gementioning
confidence: 99%
See 1 more Smart Citation
“…The bisulfite‐converted DNA was amplified by PCR with previously described primers 70, 71. The PCR products were cloned into the pCRII TOPO vector (Invitrogen), and plasmids extracted from individual clones were sequenced by GATC‐biotech (http://www.gatc-biotech.com/en/index.html).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have recently addressed this gap within the literature, reporting the restorative effects of induced neural stem cells in models of spinal cord injury and Parkinson's disease. In one study, mouse embryonic fibroblast-derived induced neural stem cells were transplanted into the contused thoracic spinal cord of rats [151] . Following transplantation, induced neural stem cells lost their stem cell identity and differentiated into neurons, astrocytes, and oligodendrocytes, with synaptic formation observed between host and transplanted neurons.…”
Section: Clinical Applications Of Induced Neural Cell Typesmentioning
confidence: 99%